Politiques scolaires et choix de carrière : l'École algérienne vue par les médias - Hocine Khelfaoui (Les éditions de la Maison des sciences de l'Homme, 2002)
In Algeria the press is an important vector of sharing out information on schools. Although the press assumes its usual functions of arranging information, it does, in the Algerian context, compensate the lack of information on schools and the surroundings. With an autarchic school system, which can almost be qualified of autistic, the mass media reveal the system underneath and contribute to its knowledge and legibility. But far from being only an information network it contributes to the school policy debates which acknowledges the main political parties. The paper will retrace at first, the history of the Algerian media and their relation with education, then propose an analysis of the impact of the media on two levels: first, the different school policies as suggested by the different social political forces and arranged by the state, and second, the personal choice of strategies and career.